Determinan Kualitas Audit Dengan Tenure Audit Sebagai Variabel Moderasi - Farhah Nabila; Siti Hartinah (Universitas Muhammadiyah Jakarta, 2021)
This study aims to examine various factors that can affect audit quality moderated by tenure audit. The data analysis method used is the Moderated Regression Analysis. The results of this study indicate that independence, audit fees, and tenure audits have a positive and significant influence on audit quality. Meanwhile, time budget pressure has a negative and significant effect on audit quality. And tenure audit moderates independence, time budget pressure, audit fees have a positive and significant influence